(untitled) - Baker, Blanche; Katz, Ross; 1971-; Bacon, Kevin; 1958-; 1956- (HBO Home Video, 2009)
Follows Marine Lt. Col. Michael Strobl as he escorts the coffin carrying Lance Corporal Chance Phelps back to Phelps hometown in Wyoming.
Keywords: Soldiers; Drama; Drama; Drama; Military funerals; Marines; Television programs for the hearing impaired; Video recordings for the hearing impaired; DVD-Video discs; Made-for-TV movies